Childbirth and women's labour market transitions in India - Rosa Abraham; Rahul Lahoti; Hema Swaminathan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
The impact of childbirth on the labour market participation of women has been discussed extensively in the context of developed countries, constraints on mothers labour market participation and earnings being characterized as the motherhood penalty . In the developing country context, and specifically for India, similar studies are limited, primarily due to the lack of longitudinal data. In this paper, using a Life History Calendar approach, we collect retrospective information on major events (education, marriage, and childbirth) and the concurrent employment status of men and women over their adult lives. Using an event study method, we estimate the impact of first childbirth on women s labour market participation. Our main finding is that the birth of the first child does not impose a penalty on the mother s labour supply. While, overall, employment does not show any association with childbirth, women s paid work actually registers a significant increase two to three years post childbirth even after controlling for several other factors. The life history analysis also shows that, conditional on participating in the labour market, women are unlikely to have several episodes of entry and exit. We hypothesize that, in a developing country context such as India s, motherhood may not be accompanied by a penalty in terms of labour market participation given the predominance of informal and flexible employment arrangements and the early age of marriage and childbirth for women.
Additional information: Update (October 2021): a new version of this working paper is available as WIDER Working Paper 2021/149, https://doi.org/10.35188/UNU-WIDER/2021/089-4 .
Keywords: J01; J12; J13; J16; 330; motherhood penalty; childbirth; event study; life history calendar; India